COVID-19 and the impact on the student delivery of exercise physiology services: a mixed method study - Teneale McGuckin; Lisa Simmons; Denise Turner (Bond University, 2022)
_Introduction:_ The COVID-19 pandemic has impacted the face-to-face delivery of exercise with social distancing restrictions preventing close contact between clients and exercise professionals. Additionally, exercise physiology students have had to adapt to these changes and use telehealth to achieve their learning outcomes. This study aimed to explore client and student perspectives of their experience with face-to-face exercise delivery prior to COVID-19 restrictions and telehealth during restrictions. _Methods:_ Clients and students were invited to complete an online survey exploring their experience with student-led exercise services prior to COVID-19 restrictions and during restrictions. Likert-scale questions were compared using a Wilcoxon test and open-ended responses were thematically analysed. _Results:_ Prior to COVID-19 restrictions, all students (n = 7) reported that providing face-to-face exercise physiology services resulted in positive learning experiences and clients (n = 12) were satisfied with their experience. During the restrictions, the client satisfaction with exercise delivery via telehealth remained high, however, students' learning experience was hindered by the restrictions. _Discussion and conclusion:_ For clients, satisfaction with the exercise delivery remained high and the convenience of telehealth were useful during a pandemic. For students, their exercise prescription and ability to assess and monitor their clients were impacted by using telehealth.